Enhancement In Resistivity Resolution Based On Data Amalgamation Technique - Bery, Andy Anderson (2015)
The 2-d electrical resistivity imaging measured resistivity distribution at the subsurface. Improvement in 2-d resistivity data quality was carried out by the data levels amalgamation (dla) technique which is based on overlapping data levels with two different arrays combination. The first study objective is to develop the numerical comparative assessment for individual array and the dla technique of two different arrays. The second objective is to improve resolution using the dla technique on two different arrays. The final objective is to validate the dla technique of two different arrays. In order to achieve all three objectives, the study was carried out in three different phases. The first phase involved 2-d computerized models or namely synthetic models and a field model are presented. Five different synthetic models are created and used to investigate the imaging capabilities using four different arrays. In second phase, the numerical comparative assessment is introduced for the individual array and the dla technique. The two best and suitable arrays were determined based on the numerical comparative analysis results. In phase three, validation of the dla technique using two best and suitable arrays are applied to the actual field surveys. Based on the numerical comparative assessment for both 2-d computerized models and a field model, it shows that the dla technique of pole-dipole (p-d) and wenner- schlumberger (w-s) arrays are able to provide good data quality of image.